Relationship between Maternal Haemoglobin and Fetal Weight - Rana, Sadikchya Singh; Sharma, S; Chand, A; Malla, R (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: This study was done to determine the relationship between maternal haemoglobin and fetal weight. Methods: This study was carried out at Paropakar Maternity and Women’s Hospital in 491 primigravidas with full term singleton pregnancy. The study population was divided into two groups, one who had haemoglobin 10 gm% or more and the other women having haemoglobin less than 10 gm%. Fetal weight as the outcome variable was compared between anaemic and nonanaemic mothers and the relation between maternal haemoglobin and fetal weight was studied. Results: The prevalence of anaemia was 46.2% out of which 99.5% had mild anaemia and 0.5% had moderate anaemia. Mean haemoglobin level was 11.54 gm% among non anaemic women and mean birth weight was 2.9 kg in this group whereas mean haemoglobin level was 9.2 gm% in anaemic women and mean birth weight was 2.6 kg in this group and 60% babies had low birth weight (<2.5 kg) born to anaemic women (haemoglobin <10 gm%), and 40% babies had fetal weight >2.5 kg. Similarly babies born to nonanaemic women (haemoglobin >10 gm%) 18.1% had LBW and 81.9% had fetal weight >2.5 kg. The risk of low birth weight was 6.8 times higher among anaemic mothers as compared to non- anaemic mothers which was statistically significant with p-value of 0.0001 (OR 6.80 95% CI, 3.83-12.12). Conclusions: Anemia in pregnancy is one of the causes for poor fetal outcome. Proper antenatal care and counseling can reduce the incidence of anaemia in pregnancy. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 37-40 DOI: http://dx.doi.org/10.3126/njog.v8i1.8860